Art and existence in the phenomenological aesthetics of Maurice Merleau-Ponty - Вячеславова, О. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article discusses the recent works of M. Merleau-Ponty, with the aim of an explication of the aesthetic aspects of the phenomenological ontology of this philosopher. The specificity of the concept of M. Merleau-Ponty's approach to the fine arts is revealed in the article. It is the negation of the constitutive idealism, in the emphasis of noematic analysis in contrast to the study of noetic act. The article considers the position of M. Merleau-Ponty on the question of the genesis of polysemy, analyzes his critique of representation in art, identifies the understanding of the philosopher of the ontological nature of art. The author points to the aesthetic aspects of genetic phenomenology M. Merleau-Ponty associated with the thematization of the perceptual sense and the transition from it to the linguistic meaning.